TOTAL QUALITY MANAGEMENT UNTUK PENINGKATAN KUALITAS PELAYANAN - -, Sunarso (Universitas Slamet Riyadi, 2006)
ABSTRACT A company should produce and serve high quality products and services with low prices by an effective promotion and a better service compared in order to develop or even survive in a competition. Many companies in Japan achieve global success as a result of their high quality products. To obtain high profit in a hard competition, however, there is no other way but applying Total Quality Management for the company. There is a close relation in quality of products (good and services), customer satisfaction, and company’s profit. The better quality product, will give the higher customer satisfaction. In the meantime, it automatically raises the price, which apparently the production only needs low cost. Thus, quality improvement program is purposed to raise company’s profit. Keywords: TQM, quality service, customer satisfaction, managerial performance.